Delineation of management zones to improve nitrogen management of wheat - Peralta, Nahuel Raúl (2015)
Site-specific management of N (NSSM) is an attractive and intuitive approach to increasing N fertilizer use efficiency (NUE) of agricultural systems by adjusting fertilizer rates to the soil characteristics. The objective of this study is to assess: whether delineating of management zone (MZ) within fields improves NUE in wheat (. Triticum aestivum L.). This research was carried out at 5 commercial fields (between 26 and 84. ha), located in the south-eastern portion of the Province of Buenos Aires, Argentina. The MZ were delineated by using georeferenced measurements of apparent soil electrical conductivity, terrain elevation and soil depth. Spatially referenced wheat yields were recorded with a yield monitor equipped with DGPS. The interaction effect was significant (. p<. 0.05) in most fields, thus indicating that the response to N fertilization is different among MZ. Also, NUE was significantly different (. p<. 0.05) among MZ. The detection of soil spatial variability and the delineation of MZ are now possible on a commercial scale. The delineation of MZ affords the opportunity of variable rate application of N fertilizers on Typic Argiudolls and Petrocalcic Paleudolls, and the minimization of pollution risk due to an excessive application of resources.